Pembentukan Kecamatan Pesanggrahan sebagai Kecamatan Tangguh Bencana di Kota Jakarta Selatan - Fathin Aulia Rahman; Haris Achadi (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2023)
Potential disasters in South Jakarta include floods, landslides, fires, disease epidemics and social conflicts. There are 25 flood location points in South Jakarta and it is the Administrative City with the highest number of flood location points in DKI Jakarta. Pesanggrahan sub-district is one of the sub-districts passed by the Pesanggrahan watershed which is part of a series of watersheds that originate at Mount Salak and flow through several areas. The concept of resilience is important for every region or region to have. Resilience or toughness is a system of ability to anticipate, avoid, or resist, adapt and spring back due to disturbances or crises due to disasters. So that it is necessary to establish disaster resilient institutions in the sub-district area or at the sub-district level in order to increase community resilience to facing disasters. Therefore, we as the academic community of Budi Luhur University carry out assistance in the formation of a disaster-resilient sub-district in Pesanggrahan District, which is expected to form a community of people engaged in disaster management.